Pengantaraan Orang-orang Kudus: Dasar Historis dan Doktrinalnya - Laksito, Petrus Canisius Edi (Institutum Ioannis Mariae Vianney Surabayanum, 2024)
This article wants to explore the historical and doctrinal basis for the practice of praying through the intercession of saints, which is commonly found in the Catholic Church. For that purpose, it will study the historical context of its origin and its doctrinal basis originating from the documents of councils. From the study of these sources, it is hoped that we can find the authentic spirit behind the practice of supplicating prayer through the intercession of saints. It is also hoped that, with a proper understanding of its history in the Church and the Church teaching on it, abuse can be avoided, and correct practice found support. For this reason, the discussion will be maintained by a study on the historical context of the practice and of the development of the doctrine found in the Magisterium of the councils. Yet the general theological framework of the Second Vatican Council will be presented first, so that the theological vision of the theme in the modern era could be placed as our basic understanding. But as it is also necessary to present the historical background of this practice, the discussion should also be supplied with this historical background. With this background, it is hoped that the idea of the teachings outlined by the councils, from the beginning up to the Second Vatican Council, can be better understood.